1966
DOI: 10.5636/jgg.18.257
|View full text |Cite
|
Sign up to set email alerts
|

Recent Investigations of Hydromagnetic Emissions Part II. Theoretical Interpretation

Abstract: Recent experimental and theoretical work suggests the hypothesis that hydromagnetic (hm) emissions are hydromagnetic wave packets guided by field lines as they bounce back and forth between hemispheres of the earth. As such they are analogous to whistlers, and one test of the hypothesis is the quantitative calculation of plasma densities in the outer magnetosphere and their comparison with whistler densities closer to the earth.Many hm emission exhibit measurable dispersion when displayed in the form of sonagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1966
1966
1970
1970

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In all of these models, the basic resonance takes place at some fraction of the cyclotron frequency owing to Doppler shifting, and the spacing is indicative of the latitudinal bounce time of either the field-guided energy packet or of the particles that are amplifying the wave [Tepley and Wentworth, 1965]. It has been demonstrated by several authors [Obayashi, 1965;Gendrin and Troitskaya, 1965;Wentworth, 1965] that protons, not electrons, are the most reasonable source for this interaction.…”
mentioning
confidence: 99%
“…In all of these models, the basic resonance takes place at some fraction of the cyclotron frequency owing to Doppler shifting, and the spacing is indicative of the latitudinal bounce time of either the field-guided energy packet or of the particles that are amplifying the wave [Tepley and Wentworth, 1965]. It has been demonstrated by several authors [Obayashi, 1965;Gendrin and Troitskaya, 1965;Wentworth, 1965] that protons, not electrons, are the most reasonable source for this interaction.…”
mentioning
confidence: 99%
“…Thus the plasma density can be determined almost uniquely (within the accuracy of present observation), in particular at the longer periods (for example, longer (b) Comparison with other results. Much information on the magnetospheric plasma density based on ground observations has been obtained from whistler investigations (Carpenter 1963, Carpenter and Smith 1964, Angerami and Carpenter 1966, and also from micropulsation studies (Obayashi and Jacobs 1958, Wentworth 1965, Watanabe 1965. Whistler studies have suggested that the electron density suddenly drops by a factor of 50 or more at distances between 3 and 5 Re (the knee), and has comparatively low values beyond the knee.…”
Section: Resultsmentioning
confidence: 99%
“…Whistler studies have suggested that the electron density suddenly drops by a factor of 50 or more at distances between 3 and 5 Re (the knee), and has comparatively low values beyond the knee. Wentworth (1965Wentworth ( , 1966 and Watanabe (1965) also deduced relatively low values of the plasma density (0.5-50 particles/cm3 in the region L=5-9) using pearl micropulsations (period 0.2-5 sec.). Since micropulsations of this period are believed to be generated at a distance of L=4-6 in the equatorial region (Jacks 1966) the resulting lower values of plasma density agree with the lower values in the outer region of the knee estimated from whistler studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But, for the same reasons, the field of diagnosis that can be made from ULF observations covers a wide range of magnetospheric problems Troitskaya and Gul'elmi, 1967;. We are not interested here in the determination of electron density profiles (Dowden and Emery, 1965;Watanabe, 1965;Wentworth, 1966;Kenneyetal., 1968;Liemohn etal., 1968). We will deal only with questions which are related to the understanding of magnetospheric storms: localization and bulk motion of the region of interaction, energy and flux of the interacting particles.…”
Section: Use Of the Gyroresonant Theory As A Tool For Diagnosismentioning
confidence: 99%